A MAYA CURIA REGIS: EVIDENCE FOR A HIERARCHICAL SPECIALIST ORDER AT XULTUN, GUATEMALA. Issue 2 (28th February 2017) - Saturno, William; Rossi, Franco D.; Stuart, David; Hurst, Heather
Abstract: This article presents an in-depth analysis of an important mural painting discovered within Structure 10K2 of the Los Sabios Group at the Classic Maya site of Xultun, Guatemala. We first discuss the composition of the mural scene and its central protagonist, a Late Classic period (a.d. 550–900) ruler of Xultun named Yax We'nel Chan K'inich, suggesting that it presents a ritual performance associated with an ancient New Year ceremony. Several attendant figures in the mural are labeled as members of a specialist order or category called Taaj, "obsidian, " and are marked by an unusual shared appearance. This "obsidian order" exhibits internal hierarchical ranking and is attested at other Classic Maya centers. In addition to discussing the overall content of the Xultun mural scene, we conduct a focused inquiry into these various Taaj individuals by presenting associated archaeological evidence and considering related epigraphic data. Through this analysis of the Taaj, we shed light on a previously unknown aspect of Maya courtly life and organization that is relevant to models of sovereignty, governance, and ritual performance in the Classic Maya world.